(untitled) (American Journal of Business Management, Economics and Banking, 2024)
The current research aims to examine the views of previous literature regarding customer hope in virtual brand communities. In today’s world, customers hope for a better experience when they look to make a purchase. They also look for convenience, affordability, and quality that goes above and beyond. They have suffered in the past, so virtual brands must take these expectations seriously, and strive to meet or exceed them in order to build a lasting relationship with their customers. Virtual brands must be willing to put in the hard work and go the extra mile to make sure their customers are happy. This means ensuring that their purchases are of the highest quality, and that their products are affordable. Hope is the tangible ability to find paths to achieving enjoyable goals, along with the perceived motivation to use those paths to achieve the desired goal.